How do significant others influence our driving? A descriptive study of ego–alter dyads in a college population. (19th May 2017) - Beck, Kenneth; Watters, Samantha
ABSTRACT: Objectives : The purpose of this investigation was to describe the mutual influences between drivers and their significant others in a sample of college students, using a social network perspective. Methods : A web-based survey was made of 65 dyads of drivers and their significant others, in order to examine areas of mutual influence concerning driving. Measures were taken of their frequency of risky driving, including how often they drive, talk on the cell phone, or text with each other while driving. They were also asked whether they have influenced or been influenced by each other to drive safer or in a more risky manner. Results : The dyads were very similar in how frequently they drive as well as talk to each other on the phone while driving. However, they were unlikely to feel that their driving was influenced by each other, with only 17% of the drivers and 19% of the significant others saying that they have been overtly influenced by (or have influenced) each other's driving behavior often or most of the time. Yet, most (67.7% and 72.1%) said they have ever encouraged or been encouraged by each other to drive more safely, mainly by being told to reduce their speed. In both sets of drivers in these dyads, talking to and texting their significant other while driving was related to risky driving. Conclusions : These findings suggest that a similarity exits in the driving patterns of young drivers and their significant others, especially concerning talking to each other on the phone while driving. The largest degree of overt social influence appears to center around avoidance of behaviors perceived to be associated with getting a traffic citation. Implications for safety campaign development and future research are presented.